The effect of breed and body score condition on the quality and viability of epididymal bovine sperm from post mortem bull by in vitro collection method - Budiyanto, Agung (2012)
This study was to assess two factors wheather has an effect on the quality of spermatozoa collected frum didymis. This experimet based of the effect of breed Peranakan Ongole/PO and Crossbreed :Simmental POSimpo, Limousine PO/Limpo and body conditionscore (BCS) of bull. Sperm samples were collected by shing of epiydimis postmortem. Motility and lives and death sperm stain by oosin negrosin. The sificance of semen quality was analyzed among the groups by two-way ANOVA and Tukey-Kramer sest value of less than 0.05 was regarded as significant. The results showed that motility of local breed PO significantly higher (PC0.05) than the crossbreed bull Limpo and Simpo, 53.3%, 36.6% and 36.0% spectively. Viability (live and death) of the sperm showed that PO, Limpo dan Simpo, 78,0%, 69.5% and 54.0% respectively. The results showed that the hall with BCS 3 and 3.5 has significantly higher motility and sability than the bull with 2.5 (46.9, 51.7% and 26.7 %) respectively. Visbility based on BCS showed that ball with BCS 3 and 3.5 has significantly higher than Bull with BCS 2.5 (66.8 x.2 % and 50.0%) pectively. In conclusion, local breed bull (PO) epididymis spermatozoa have better motility and viability than the crossbreed bull Simpo and Limpo). Moreover, ball with BCS 3 and 3.5 has better motility and viability than 2.5 BCS standard. Key words: sperm, epidydimis, motility, live and death sperm, quality, breed and BCS